2015
DOI: 10.1016/j.ssresearch.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the devaluation of vulnerable groups: A novel application of Institutional Anomie Theory

Abstract: Prejudices legitimize the discrimination against groups by declaring them to be of unequal, especially of less, worth. This legitimizing power is highly relevant in social conflicts of modern societies that are governed by market-oriented value systems. However, prejudice research has yet to be linked to sociological discourses on the marketization of society. We argue that Institutional Anomie Theory (IAT), a theory originally developed to explain crime rates, offers a fruitful macro-sociological framework fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 28 publications
4
34
1
4
Order By: Relevance
“…Of particular relevance for present purposes are efforts by Hövermann et al (2015aHövermann et al ( , 2015b to derive from IAT implications for an individual-level, social psychological orientation that they characterized as a 'marketized mentality'. Such a mentality entails an especially strong commitment to the principal values, evaluative standards, and logics of the market economy.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular relevance for present purposes are efforts by Hövermann et al (2015aHövermann et al ( , 2015b to derive from IAT implications for an individual-level, social psychological orientation that they characterized as a 'marketized mentality'. Such a mentality entails an especially strong commitment to the principal values, evaluative standards, and logics of the market economy.…”
Section: Introductionmentioning
confidence: 99%
“…Na medida em que decaem a confiança nas instituições e a identidade nacional, enquanto consciência de pertencimento e sentimento de ligação ao país, crescem os sentimentos de anomia (normless) e de privação relativa. Vários estudos demostram que sujeitos desligados da estrutura social, insatisfeitos e anômicos são os mais susceptíveis a comportamentos disruptivos; seja de protesto político, seja de vandalismo e criminalidade ou ainda de rejeição às minorias sociais (Hövermann, Groß, Zick, & Messner, 2015;McDill, 1961;Srole, 1956).…”
Section: Considerações Finaisunclassified
“…In a previous study, Hövermann and colleagues (2015) have reported evidence suggesting that insights from IAT can be usefully applied to explain devaluations toward selected ‘unprofitable’ groups. The present analyses go beyond this prior work by incorporating anomia as well as other important predictors of prejudices in the model to determine if marketization processes exhibit any effect on prejudices net of a wider range of well-established covariates.…”
Section: Introductionmentioning
confidence: 99%